2012
DOI: 10.1517/13543776.2012.709237
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin and its derivatives: a patent review

Abstract: At present, screening for anticancer shikonin derivatives is based on cellular level to find compounds with stronger cytotoxicity. Though several compounds have been discovered with striking cytotoxicity in vitro, however, no selectivity was observed and undoubtedly, the further outcomes have been disappointing because of their great damage to normal cells. Meanwhile, the presumed mechanisms of action are also established in terms of their cytotoxicity. From a pharmacological point of view, most of the shikoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 74 publications
0
52
0
1
Order By: Relevance
“…High-dose Shikonin induces cancer cell necroptosis in OS, while delivery of high-dose Shikonin locally into the OS may be challenging and could have potent side-effects [23][24][25]. Thus, in our previous study and here, we analyzed the effects of low-dose Shinkonin on the invasiveness of OS, as well as the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…High-dose Shikonin induces cancer cell necroptosis in OS, while delivery of high-dose Shikonin locally into the OS may be challenging and could have potent side-effects [23][24][25]. Thus, in our previous study and here, we analyzed the effects of low-dose Shinkonin on the invasiveness of OS, as well as the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…Shikonin is a purified constituent from a Chinese medicinal herb Lithospermum erythrorhixon [23][24][25]. Shikonin has demonstrated anti-tumor potent, in which it induces cancer cell apoptosis and necroptosis [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shikonin has been found to have anti-tumor effect through inducing cancer cell apoptosis and necroptosis [32][33][34]. Recently, we reported that high dose of shikonin had prompt but profound anti-tumor effect on both primary and metastatic OS, through inducing RIP1-and RIP3-dependent cancer cell necroptosis [35].…”
Section: Introductionmentioning
confidence: 98%
“…Shikonin is an effective constituent that was purified from Lithospermum erythrorhizon, a Chinese medicinal herb [32][33][34]. Shikonin has been found to have anti-tumor effect through inducing cancer cell apoptosis and necroptosis [32][33][34].…”
Section: Introductionmentioning
confidence: 99%